The Expanded Risk Score in Rheumatoid Arthritis (ERS-RA): performance of a disease-specific calculator in comparison with the traditional prediction scores in the assessment of the 10-year risk of cardiovascular disease in patients with rheumatoid arthritis (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY To assess the performance of the Expanded Risk Score in Rheumatoid Arthritis (ERS-RA), a disease-specific cardiovascular disease (CVD) prediction score, in evaluating the 10-year risk, in comparison with other traditional algorithms in patients with rheumatoid arthritis (RA). METHODS Consecutive RA patients, aged 40–75 years, without established CVD, were included. We calculated the disease-specific ERS-RA and four traditional CVD prediction scores: the modified Systematic Coronary Risk Evaluation (mSCORE), the Framingham Risk Score using body mass index (FRS BMI), the calculator developed by the American College of Cardiology / American Heart Association in 2013 (ACC/AHA 2013) and the QRISK3. Subjects also underwent ultrasound assessment of the carotid arteries. The presence of a carotid intima-media thickness (CIMT) >0.90 mm or of carotid plaques identified the high-risk patients. RESULTS Of the 84 patients evaluated, 33 (39.3%), 16 (19.0%), 24 (28.6%), 25 (29.8%) and 33 (39.3%) subjects were defined as having high CVD risk according to ACC/AHA 2013, mSCORE, FRS BMI, QRISK3 and ERS-RA, respectively. Compared with the ultrasound results, all the areas under the receiver operating characteristic curves (AUC-ROC) showed good discrimination properties (0.848 – FRS BMI, 0.816 – mSCORE, 0.828 – ACC/AHA 2013, 0.844 – QRISK3, 0.869 – ESR-RA). Comparison of the AUC-ROCs did not show that discriminative ability for detecting subclinical atherosclerotic damage was improved with ESR-RA. CONCLUSIONS Using a surrogate marker of subclinical atherosclerotic organ damage as indicator of CVD burden, the newly ERS-RA risk score that incorporates specific aspects of RA performs as well as ACC/AHA 2013, mSCORE, FRS BMI and QRISK3 estimators.